ANALISIS KERENTANAN TANAH TERHADAP BAHAYA LIKUIFAKSI BERDASARKAN DATA PENGUJIAN SPT - Muhammad Kautsar Rizki; Halida Yunita; Bambang Setiawan; Zulkifli Zulkifli (Prodi Magister Teknik Sipil Unsyiah, 2021)
Aceh is a province in Indonesia that was hit significantly by the 26 December 2004 disaster. The province was also hit by the M 6.5 Pidie Jaya earthquake on 7 December 2016. Several damages induced by liquefaction, i.e., sand boils, were observed in these two seismic events. Liquefaction is defined as the transformation of granular material from a solid to a liquefied state. This Liquefaction phenomenon can cause damage to buildings and infrastructures built on it. This study presents the results of liquefaction assessment using the standard penetration test (SPT). A borehole was sunk at Rundeng Village, Johan Pahlawan sub-distrit, Aceh Barat distrit to collect the SPT data. This location was selected as several facts, i.e., low water table, built of sand layer, and high seismicity region were suggested for this Rundeng village. Three different models of Esteva (1974), Donovan (1970), and Mc Guirre (1977) were used to estimate the cyclic stress ratio (CSR). A model developed by Seed and Idriss (1982) was employed to estimate the cyclic resistance ratio (CRR). From the calculation of potential liquefaction evaluation, the cyclic stress ratio (CSR) value highly depends on the earthquake magnitude. The greater the earthquake magnitude, the greater the CSR value becomes. Soil layers from SPT data at a depth of 3,50 m – 13,00 m have a value of (N1)60cs 30 which means the soil is too dense to liquefy and classified as non-liquefiable soil. From the SPT data, it can be seen the soil will be liquefied if an earthquake with a magnitude ≥ 8 occurs.